Acute abdominal pain: Ruptured abdominal aortic aneurysm - Dávila-Hernández, Carlos Alberto (2023)
A 57-year-old male, with abdominal pain, stabbing type, sudden onset, located in hypogastrium with irradiation to the genitals, with great intensity 8/10 according to eva scale; in the hospital he presented arterial hypotension so he was treated in trauma shock; with complete abdominal ultrasound reporting in pelvic cavity image of rounded morphology of 73 x 67 mm in diameter, with walls of 9. 1 mm, consider: aortic artery aneurysm (AAA); in abdominopelvic angio-CT abdominal aorta is observed distended 107 x 71 mm, with multiple hypodense images, irregular, suggestive of hematomas, consider: Ruptured AAA; keep in mind that aortic aneurysms can occur in any of the five anatomical regions of the aorta: root, ascending thoracic, aortic arch, descending thoracic and abdominal, but are less common in the abdominal cavity.(1). AAA is a silent, progressive and potentially fatal pathology (in 90%), whose prevalence ranges from 1.5 - 5.9% in people over 50 years of age; as for its proximal extension it can be infrarenal, the most frequent, or pararenal and this in turn is divided into juxtarenal and suprarenal (2). Risk factors include: age over 65 years, male sex, smoking, family history of AAA, coronary artery disease, arterial hypertension (AHT), peripheral artery disease and previous myocardial infarction. (3). Although symptoms include severe and persistent pain in the back, abdomen, flank or groin; aneurysmal dilatation may cause nonspecific abdominal symptoms; the triad of ruptured AAA includes abdominal or flank pain, hypotension or shock, and pulsatile abdominal mass. Differential diagnosis was made with renal colic, diverticulitis, gastrointestinal tract hemorrhage, mesenteric ischemia (4). The treatment of AAA can be: Preventive: no smoking and avoid passive smoking; healthy diet: low-fat foods, limit salt content; Medical: aims to control risk factors; no intense physical activities; Surgical: in compression of adjacent structures or aneurysm diameter greater than 5.5 cm; traditional (open) or endovascular approaches are considered here (5). The patient died because he had no means of resolution.